ChemInform Abstract: Copper‐Catalyzed Cascade Cyclization for the Synthesis of Trifluoromethyl‐Substituted Spiro‐2H‐azirines from 1, 6‐Enynes. Issue 9 (February 2016) - He, Yu‐Tao; Wang, Qiang; Zhao, Jiahui; Wang, Xiao‐Zhen; Qiu, Yi‐Feng; Yang, Yu‐Chen; Hu, Jing‐Yuan; Liu, Xue‐Yuan; Liang, Yong‐Min
Abstract: A new method for the synthesis of CF3 ‐substituted spirocyclic compounds containing a unique quaternary carbon center from readily available starting materials is developed.